COST â€“ BENEFIT ANALYSIS FOR WASTE MANAGEMENT PROJECT (Case Study in Bank Sampah Malang) - Putri, Rizka Zuhriani; Wahyudi, Setyo Tri (Jurnal Ilmiah Mahasiswa FEB, 2016)
Human activities produce large amount of waste which require a good waste management and treatment.Thus, it results potential harm the human health and environment that pose by the bad waste management.There are several ways that already have done by people in the world in order to solve waste problem such as recyling without any systematic mechanism andÂ  final diposal. Furthermore, all of these ways are valued as uneffective ways in managing waste. Thus, government of Malang City proposes a waste management project named Bank Sampah Malang (BSM) in order to solve waste problem in Malang. Descriptive quantitative method is utilized to analyze the obtained information about benefit & cost and sensitivity of Bank Sampah Malang (BSM) and to measure its effectiveness from financial aspect and its impact to society. The collected data then analyzed by using NPV,Net B/C Ratio and sensitivity analysis.The findings reveals that Bank Sampah can earn capital gain from its operational activity as reflected on their profit and its other benefit. It also has passed requirement of NPV, Net B/C Ratio and sensitivity analysis in determining sustainbility of project. In sum, the project Bank Sampah Malang (BSM) has good level effectiveness in finance because it generates profit and it also results other benefit that can give positive impacts to society. Futhermore, project Bank Sampah Malang (BSM) must be continued to be exist. Keywords: Bank Sampah Malang, Cost-Benefit Analysis, NPV, Net B/C Ratio,Sensitivity Analysis.